Special people - Letch, Rachael (New York, NY : Child$1 (Bs Play International,s, 1990)
Describes such people as parents, friends, doctors, gardeners, and ballet dancers, who care about, share with, and love others, and take pride in the work they do.
Keywords: Caring -- Juvenile literature; Sharing -- Juvenile literature; Helping behavior -- Juvenile literature; Caring; Helpfulness; Occupations